2019
DOI: 10.1259/bjr.20180434
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric versus single slice measurements of core abdominal muscle for sarcopenia

Abstract: Article:Waduud, MA orcid.org/0000-0001-5567-9952, Adusumilli, P, Drozd, M orcid.org/0000-0003-0255-4624 et al. (4 more authors) (2019) Volumetric versus single slice measurements of core abdominal muscle for Sarcopenia. British Journal of Radiology, 92

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Anatomical landmarks, such as the vertebrae and other bony structures, are used as boundaries when performing volumetric measurements of adipose and muscle tissue compartments. The boundaries used for volumetric analyses include the areas between the 2 nd lumbar vertebra and sacrum [47], the 12 th thoracic vertebra and the superior aspect of the femoral head for adipose tissue and the inferior surface of the 1 st sacral vertebra for the determination of the paraspinal muscles [48], the 10 th thoracic vertebra and the 5 th lumbar vertebra [49] and the 1 st and the 5 th lumbar vertebra [50]. The literature lacks studies that would have compared the performance of different levels used for 2D single-slice BCA and volumes used for BCA in the evaluation of the likelihood of different outcomes in different diseases.…”
Section: D and 3d Measurements And The Applied Cut-off-values For The Ct-based Body Composition Metricsmentioning
confidence: 99%
“…Anatomical landmarks, such as the vertebrae and other bony structures, are used as boundaries when performing volumetric measurements of adipose and muscle tissue compartments. The boundaries used for volumetric analyses include the areas between the 2 nd lumbar vertebra and sacrum [47], the 12 th thoracic vertebra and the superior aspect of the femoral head for adipose tissue and the inferior surface of the 1 st sacral vertebra for the determination of the paraspinal muscles [48], the 10 th thoracic vertebra and the 5 th lumbar vertebra [49] and the 1 st and the 5 th lumbar vertebra [50]. The literature lacks studies that would have compared the performance of different levels used for 2D single-slice BCA and volumes used for BCA in the evaluation of the likelihood of different outcomes in different diseases.…”
Section: D and 3d Measurements And The Applied Cut-off-values For The Ct-based Body Composition Metricsmentioning
confidence: 99%
“…Furthermore, we measured the VBA at the third lumbar vertebrae instead of the fourth lumbar vertebrae, as previously evaluated by Oura et al, as we have previously shown morphometric measurements at this level to be most representative of structural volume. 20 Despite this, the margin of error in estimating patient height was comparable. Oura et al demonstrated volumetric quantification of the VBA to provide the most accurate representation of patient height.…”
Section: Discussionmentioning
confidence: 98%
“…The cross-sectional area (CSA) of muscle tissue at the level of the 3 rd lumbar spine (L3) provides reproducible evaluation of muscle size in cancer patients without the need for additional examinations. The measurements collected from a single slice CT image reveal solid evidence that correlates strongly with whole-body adipose tissue and skeletal muscle [ 15 17 ]. The common method is to manually draw the total CSA of all muscle groups at L3 or to quantify the CSA using thresholds of Hounsfield units (HU) from -29 to 150 for skeletal muscle using the available software [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%